Efficiently Managing Advance Reservations Using Lists of Free Blocks - Schneider, Joerg; Linnert, Barry (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2011: Anais do XXIII International Symposium on Computer Architecture and High Performance Computing, 2011)
Advance reservation was identified as a key technology to enable guaranteed Quality of Service and co-allocation in the Grid. Nonetheless, most Grid and local resource management systems still use the queuing approach because of the additional complexity introduced by advance reservation. A planning based resource management system has to keep track of the reservations in the future and needs a good overview on the available capacity during the negotiation of incoming reservations. For advance reservation, the resource management problem becomes a two dimensional problem. In this paper different data structures are investigated and discussed in order to fit to planning based resource management. As a result the benefits of using lists of resource allocation or free blocks are exposed. This general idea widely used to manage continuous resources is extended to cover not only the resource dimension but also the time dimension. The list of blocks approach is evaluated in a Grid level and a resource level resource management system. The extensive simulations showed a better runtime and higher reservation success rate compared with the currently favored approach of a slotted time.